Optical Detection of Macular Pigment Formation in Premature Infants - Sasano, Hiroyuki (Transl Vis Sci Technol, 2018)
PURPOSE: To demonstrate the presence of macular pigment in the retina of premature infants, and to examine its changes with age. METHODS: The participants included 40 premature infants. Infants who had received laser photocoagulation for retinopathy of prematurity were excluded. Macular pigment optical density (MPOD) was measured by fundus reflectometry using RetCam3, a digital fundus camera. The reflection imaging was performed for ROP screening. The imaging time points were from a post menstrual age (PMA) of 29 weeks 0 days to 46 weeks 5 days. RESULTS: The MPOD levels could be obtained from 39 premature infants. The levels at the first measurement ranged from 0 to 0.18 (mean 0.076, SD 0.044). The earliest time, when a nonvanishing MPOD level was obtained, was at a PMA of 33 weeks and 2 days, and that level was 0.05. The initial examination MPOD levels showed a moderate correlation with age (R(2) = 0.32, P < 0.00017). The mean MPOD levels measured each week during the follow-up period showed a very strong correlation with age (R(2) = 0.91, P < 0.0001). A regression line of MPOD = 0.0069 × age − 0.1783 was derived, where age is counted in PMA days. CONCLUSIONS: The MPOD levels of premature infants were for the first time measured in living eyes. Macular pigment increased linearly with age. TRANSLATIONAL RELEVANCE: Macular pigment increased with the development of macular morphology. This result suggested the importance of nutritional management of infants and mothers during perinatal period.